Wacana Inklusivisme dalam Buku Siswa Mata Pelajaran Pendidikan Agama Islam di Madrasah - Putri Wulansari; Fauzi Muharom (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
The PPIM National Survey on the Diversity of Student and Teacher/Lecture in School and Universities in Indonesia shows that most of them have opinions that are categorized as intolerant/very intoleran and radical/very radical. However, if viewed from the side of the action most have a tolerant and moderate tendency. The report’s result confirm a balanced proportion of inclusive/tolerant views with esclusive/intolerant views. Therefore this study using descriptive qualitative data based research literatur aims to explore and reinforce the existence of inclusivsm in 2013 curriculum student book on Islamic Education on subject Madrasas. The analysis tehnique used in the study uss content analysis by alalyzing the inclusivsm content in 2013 curriculum student book on Islamic Education subject based on inclusive attitute indicator, namely: looking positively at difference and building cooperation with different people or grups in order to achiec common goals, egalitarian, open mainded, broad-minded from the thegroup itself and various other groups and not extream. The result of the analysis in the 2013 curriculum student book hasan inclusive content with the existence of several discussion topics as tolerance, avoiding discriminatory behaviour, scientific thinnking and other discussion topics. although the persentation of the material is informative, its is necessary to develop the presentation of materal in student books on islamic religious education in Madrasas. keyword: Inklusivsm. Student book, Islamic Education and Madrasas.